Self-directed learning through gamification of mathematics lessons: Literature review and a framework for enactment - ONG, Eythan Tzeng Junn; TOH, Tin Lam (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2024)
Gamification, or the use of game-like elements for classroom instruction, has been the subject of study by educators. Currently there are no frameworks for enacting gamification in the mathematics classroom.  In this paper, we propose a framework for facilitating Mathematics teachers to implement gamification in classrooms. Through gamification, we target to nurture self-directed learners of Mathematics.  Our proposed framework is based on a systematic literature review conducted by the researchers. In our proposal, we map the use of various elements of gamification at each phase of learning through to Merrill’s First Principles of Instruction and van Hiele’s Model of Geometric Thinking. An exemplar of a lesson on geometry with the use of the framework is also presented.